Polymer blend of PLA/PHBV based bionanocomposites reinforced with nanocrystalline cellulose for potential application as packaging material - Dasan, Y.K. (Elsevier Ltd, 2017)
The current research discusses the development of poly (lactic acid) (PLA) and poly-(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) reinforced nanocrystalline cellulose bionanocomposites. The nanocrystalline cellulose was derived from waste oil palm empty fruit bunch fiber by acid hydrolysis process. The resulting nanocrystalline cellulose suspension was then surface functionalized by TEMPO-mediated oxidation and solvent exchange process. Furthermore, the PLA/PHBV/nanocrystalline cellulose bionanocomposites were produced by solvent casting method. The effect of the addition of nanocrystalline cellulose on structural, morphology, mechanical and barrier properties of bionanocomposites was investigated. The results revealed that the developed bionanocomposites showed improved mechanical properties and decrease in oxygen permeability rate. Therefore, the developed bio-based composite incorporated with an optimal composition of nanocrystalline cellulose exhibits properties as compared to the polymer blend. © 2016 Elsevier Ltd